1985
DOI: 10.3382/ps.0642341
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and its Relationship to Excess Feed Consumption, Body Weight, Egg Size, Fat Deposition, Shell Quality, and Fatty Liver Hemorrhagic Syndrome ,

Abstract: In Experiment 1, Hyline W36 caged hens were fed diets containing 1.7, 2.9, 3.5, and 4.1% calcium for 10 and 16 weeks. In Experiments 2 and 4, Dekalb XL and Hyline W36 pullets were fed diets containing 1.0, 1.7, and 3.75% calcium for 3 weeks (Exp. 2) or until 25 pullets from each group laid 7 eggs (Exp. 4). In Experiment 3 and 5, Dekalb and Hyline hens were fed diets containing 1.5 (Dekalb only), 1.75, 2.25, 2.75, and 3.75% calcium for 8 weeks. Criteria were liver, fat pad, egg and shell weights, egg specific g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 18 publications
2
8
2
Order By: Relevance
“…| Under some circumstances, dietary Ca may |be sufficiently marginal so that shell quality is 8 reduced but production is maintained. The hen 8 may then overconsume energy in an attempt to | meet Ca requirements (Scott et al, 1971; Lentf nards and and Roland, 1985). In § this study, Ca level did not appear to be a pri-| mary problem.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…| Under some circumstances, dietary Ca may |be sufficiently marginal so that shell quality is 8 reduced but production is maintained. The hen 8 may then overconsume energy in an attempt to | meet Ca requirements (Scott et al, 1971; Lentf nards and and Roland, 1985). In § this study, Ca level did not appear to be a pri-| mary problem.…”
Section: Resultsmentioning
confidence: 55%
“…(1971) found that replacing two-thirds of g limestone in a laying hen diet with oyster shell I produced an increase in feed intake. Ca intake § can be influenced by many factors, depending E on dietary Ca level and production rate of the .2 hen (Roland, 1985). For example, if dietary Ca £ exceeds the hen's nutrient requirement without s reducing palatability, a reduction in energy con-| sumption will result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation, 1984) because of the lower Ca availability to older hens. However, if dietary calcium becomes too excessive, feed palatability, and thus feed consumption, is reduced (Roland et al 1985). Moreover, in the experiment of Holder and Huntley (1978) there were no differences in egg shell thickness and Ca percentage in shells between eggs laid by hens given 2.5 or 3.5% Ca in diets.…”
Section: Ca Levelmentioning
confidence: 81%
“…Hens given too much Ca in their diets may reduce their feed intake, lowering egg production and egg size (Roland et al 1985). Too little Ca in the diet reduces egg production and shell quality (Abdallah et al 1993).…”
Section: Discussionmentioning
confidence: 99%